Tax Non-avoidance as a Missing Piece of the Puzzle in the CSR Agenda in Poland - Filipczyk, Hanna (Annales. Etyka w Życiu Gospodarczym, 2015)
The commitment not to engage in tax avoidance – to refrain from using aggressive tax planning techniques – has not become part of the corporate social responsibility agenda in Poland. The purpose of this paper is to examine justificatory and explanatory reasons of that significant absence. The analysis unfolds in the following way. After setting out the necessary terminological background, I present main results of the limited empirical study of selected CSR documents, in order to substantiate the claim that tax avoidance is a theme absent from the CSR programs in Poland. Then I put forward the contention that this commitment should be included in such programs, as prima facie justified, and address a selection of objections that can be raised to defeat this contention. Finally, in the last section of the paper, I briefly comment on possible reasons of this absence and show how they elucidate the nature of CSR.